Transdisciplinary Research for Sustainable Development: Diverse and Best-Practice at European Technical Universities - LEURS Inge; ROSTEK Katarzyna; WIECK Kathrin; BACKHAUS Julia; OROZCO-MESSANA Javier (Foundations of Management)
As societal challenges grow, so does the role of universities in finding social and technological solutions. Technical universities are prominent in educating future innovators and developing desired technological and social change. This paper seeks to identify commonalities and better understand differences to develop strategies for mutual support and exchange of best practices. The methodological approach focuses on three questions concerning 1) the common understanding of transdisciplinary, 2) the diversity of transdisciplinary approaches to sustainable development, and 3) the different institutional structures that enable and promote transdisciplinary approaches to sustainability. The qualitative exploratory research suggests that a higher level of societal engagement in scientific research positively impacts societal transformation towards sustainability. This research is also a first step towards making transdisciplinary research at technical universities more visible and transparent to provide better support and create a mutual learning environment for discussing and continuously developing strategies for organizational change.